Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Publisher: Norges jordskiftedommer- og landmålersamband Place: Oslo
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

Temperature, height and humidity - Schumacher, Nils Jörgen; Hisdal, Vidar (Meteorology I, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; meteorologi

Upper winds over an Antarctic Station - Robin, Gordon de Quetteville (Quarterly Journal of the Royal Meteorological Society, 1957)
Preliminary results from the Norwegian-British-Swedish Antarctic expedition 1949-52. A preliminary note on the upper-air temperatures over Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition 1949-1952, has already been published by Nils Jorgen Schumacher (1955). This note is intended to throw further light on some points raised in Schumacher's paper and to outline the general pattern of upper winds over Maudheim. Owing to the use of a radio theodolite, the data gave a representative picture of the wind structure over an Antarctic station without the excessive bias of previous observations which were limited to periods of clear weather. The detailed report and discussion of aerological observations made at Maudheim will be published shortly by the Norwegian Polar Institute.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; meteorologi

Upper Air Temperatures over an Antarctic Station: A preliminary note by - Schumacher, Nils Jørgen (Tellus, 1955)
Publisher: Taylor & Francis
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Bouvetøya - Bureau, Weather (Weather Bureau, 1954)
Pages: [14] s. Place: Pretoria
Keywords: Bouvetøya; ekspedisjoner; historie; meteorologi

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

Verdien av de meteorologiske observasjoner fra hvalkokeriene = The value of meteorological observations from whaling factory ships - Vowinckel, E (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; klima; meteorologi; observasjoner

Die norwegisch-britisch-schwedische Antarktisexpedition 1949 bis 1952 - Schytt, Valter (Die Erde, 1953)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; meteorologi

The Maudheim Expedition 1949-52 : part I - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

The Maudheim Expedition 1949-52 : part II - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Meteorologiske observasjoner på norske hvalkokerier = Meteorological observations on Norwegian factory ships - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; meteorologi